IMPLEMENTATION OF TAHFIDZ HOUSE FINANCING MANAGEMENT FOR TODDLERS AND CHILDREN (RUTABA) SIDOARJO - Fajar Tirandicha; Wildan Rizki Ramadan; Imelda Dian Rahmawati (PT. Antis International Publisher, 2024)
General Background: Islamic education plays a critical role in shaping individuals who are not only academically knowledgeable but also morally resilient, capable of addressing contemporary challenges. Specific Background: Tahfidz Al-Qur'an education, aimed at equipping students with the ability to memorize and understand the Qur'an, has seen rapid growth in Indonesia, with more than 4,500 tahfidz institutions established. Knowledge Gap: However, despite this expansion, many institutions, including the Rumah Tahfidz Toddlers and Children (RUTABA) in Sidoarjo, face significant challenges in financing management, such as inadequate transparency and inefficient fund allocation. Aims: This study aims to examine the implementation of financing management at RUTABA Sidoarjo, analyzing its financial planning, income sources, and fund allocation strategies to support its educational programs. Results: The study found that RUTABA Sidoarjo relies heavily on tuition fees from students and occasional community donations but has yet to explore more sustainable funding sources, such as government assistance or community social funds. Its financial management involves annual planning, implementation, and auditing, adhering to transparency and accountability principles. Novelty: The research highlights the institution's potential to enhance its financial sustainability by tapping into additional funding sources like government grants and waqf agencies, which are currently underutilized. Implications: The findings suggest that improving financial management strategies and diversifying funding sources can significantly enhance the quality and reach of Islamic education institutions like RUTABA Sidoarjo, ultimately contributing to better educational outcomes and broader access for underserved communities.